2005
DOI: 10.1590/s0004-28032005000100008
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation and apoptosis in gastric cancer and intestinal metaplasia

Abstract: The positivity of bcl-2 was higher in metaplasia and probably is involved in the progression of carcinogenesis. p53 was negative in metaplasia and positive in more than half of the gastric cancer, mostly in stage IV, suggesting a late event in gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 17 publications
1
12
1
6
Order By: Relevance
“…According to our fi ndings, increased proliferative activity in gastric cancer is associated with increased level of apoptosis. These fi ndings are agreeing with the literature data [8,9].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…According to our fi ndings, increased proliferative activity in gastric cancer is associated with increased level of apoptosis. These fi ndings are agreeing with the literature data [8,9].…”
Section: Resultssupporting
confidence: 94%
“…According to N. M. Fonores et al [8] the indices of cell proliferation and apoptosis progressively increase with increasing the depth of the intestinal-type gastric adenocarcinoma invasion. L. Xiao et al [9] indicated that the intestinal-type gastric adenocarcinoma is characterized by the higher expression level of caspase 3 and p53 (in comparison with the diffuse-type gastric adenocarcinoma), but the correlation between the expression levels of Ki-67, p53, caspase 3 and the depth of the tumor invasion was not identifi ed.…”
Section: материалы и методыmentioning
confidence: 99%
“…This alteration is involved in the carcinogenesis of gastric cancer, although this is not an independent factor (44) . Some authors suggest its relation to late events of gastric cancer (8,15) . Conversely, Ki-67 is a marker of cell proliferation and related to the prognosis of gastric cancer (70) .…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is not only a disease with abnormal cell proliferation and differentiation, but also a disease with abnormal apoptosis [16,17] . Increased apoptosis in human gastric cancer cells could be observed after treatment with 5-fluorouracil, cisplatin, etc.…”
Section: Figure 1 Propidium Iodide (Pi) Staining For Flow Cytometric mentioning
confidence: 99%